An evidence-based nursing practice affects stress state, coagulation, complications and quality of life in patients with upper gastrointestinal bleeding in the emergency department: a retrospective observational study - Juan Hu; Chengli Zhou; Ling Feng; YuHong Yang (BMC Gastroenterology)
Abstract Background Acute gastrointestinal bleeding (GIB) is a common surgical emergency digestive system disorder with high morbidity and mortality. Aim This study sought to explore effects of evidence-based nursing practice (ENP) procedures on stress state, coagulation function, complications in patients with upper GIB (UGIB) and quantify of life in emergency department. Methods This study was a retrospective analysis and a total of 120 patients with UGIB were enrolled and divided into an experimental group with ENP interventions and a reference group with traditional nursing according to different nursing programs. The physiological stress indicators (epinephrine, norepinephrine, plasma cortisol), psychological stress indicators [anxiety self-assessment scale (SAS), depression self-assessment scale (SDS)], coagulation function indicators [prothrombin time (PT), prothrombin time (TT), D-dimer (D-D), fibrinogen (FIB)], complication rate and quality of life were analyzed. Results After nursing intervention, epinephrine, norepinephrine and plasma cortisol, SDS and SAS scores were decreased in the experimental group relative to the reference group (all P < 0.001). After nursing intervention, the levels of PT, TT and D-D in both groups were lower and the FIB was higher than before intervention (all P < 0.001), and the improvement of coagulation function indexes in experimental group after nursing was better than that in reference group (P < 0.001). The incidence of complications in the experimental group was lower than that in the reference group (P = 0.04). The higher quality of life scores after nursing intervention was validated in the experimental group relative to the reference group (P < 0.001). Conclusion ENP improved stress response, coagulation function, quality of life, and reduced incidence of complications in UGIB patients, indicating potential for clinical application.